Homoleptic [ONO]2Ti(IV) type complexes of amino-acid-tethered phenolato, Schiff-base ligands: Synthesis, characterization, time-resolved fluorescence spectroscopy, and cytotoxicity against ovarian and colon cancer cells - Shpilt, Zohar; Manne, Rajesh; Rahman, M. A.; Mitra, Sivaprasad; Tiekink, Edward R. T. *; Baul, T. S. B.; Tshuva, E. Y. (Wiley, 2019)
Six homoleptic Ti(IV) compounds of dianionic tridentate Schiff base ligands were synthesized from chiral amino acids, 2-hydroxybenzaldehyde and Ti(OiPr)4. The compounds were spectroscopically characterized and the molecular geometries were established by X-ray crystallography. The ligands coordinated the titanium via carboxylate-O-, imine-N-, and phenoxide-O atoms. Two isomers were identified; each based on a trans-N2O4 donor set, but one with trans carboxylate-O atoms and another with each carboxylate-O atom trans to a phenoxide-O atom. Photophysical profiles exhibited faster excited-state relaxation in the solid phase than in solution. Marked cytotoxicities were recorded toward human ovarian A2780 and colon HT-29 cancer cells with IC50 values ranging between 23±2 and 103±3 µM. Comparative hydrolytic stability studies by NMR in 10% D2O solutions provided t1/2 values of up to 15±2 h, with little correlation to cytotoxicity implying a role of hydrolysis products in the reactivity and identifying steric bulk as a contributor to stability and solubility.